Investigation of the Benzene Concentration and Distribution in Tehran Using Geographic Information System Modelling - Mohammad reza khani; Mina Ghahrchi; Edris Bazrafshan; Yousef Dadban Shahamat (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Air pollution has been recognized as the most important environmental risk factor worldwide. Benzene which is one of the four pollutants attributed to BTEX (Benzene, Toluene, Ethylbenzene, and Xylene) has been proven to be a carcinogenic component. These pollutants can be easily absorbed and taken into the body via inhalation. With this background in mind, the present study aimed to investigate the concentration of benzene and its zoning in Tehran air using Geographic Information System (GIS)  within 2016-2017. Methods: In the present study, 26 sampling stations were selected in different parts of the city and sampled in four seasons to determine benzene concentration, as well as other meteorological parameters, such as temperature, humidity, and wind velocity. Thereafter, the obtained data were analyzed in SPSS software (version 22) using the one-way analysis of variance and correlation. Subsequently, modeling of pollutant distribution was performed using ArcGIS software.  Results: The obtained results demonstrated that in terms of location, the maximum and minimum annual mean concentrations of benzene were calculated at 45.12±15 and 12.36±8 μg/m3, respectively, in the center and north of the city. Temporally, the maximum and minimum values were measured at 47±17 µg/m3 in autumn and 9.82±7 µg/m3 in spring, respectively. Statistical analysis revealed that emission of this pollutant showed a significant relationship with geographical direction and wind velocity (P<0.01). Conclusion: The average annual concentration of benzene in different geographical areas of Tehran was higher than the standard values of clean air. Therefore, it is suggested that fundamental measures be implemented to control this chemical compound.